STATUS KUALITAS AIR DAN UPAYA KONSERVASI SUMBERDAYA LAHAN DI DAS CITARUM HULU, KABUPATEN BANDUNG - Muhammad Widyar Rahman; M. Yanuar Jarwadi Purwanto; Suprihatin Suprihatin (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2014)
Relationships between water quality and catchment characteristics are examined for rivers in the Upper sub Watersheds of Citarum using a GIS-based approach. The study aimed to analyze the relationship of type of land cover and water quality parameters in response to surface runoff. The multiple linear regression model was evaluated to demonstrate the relationship between the both variables. Stepwise multiple linear regressions demonstrated that agriculture and settlement land cover type was able to describe the overall water quality status. Physico-chemicals of water quality parameters could be sufficiently predicted using one land use/land cover type. Stepwise regression results showed that paddy field were significantly related to pH, DO, BOD and COD.Forestrelated significantly to TDS and temperature in dry periods. Water quality parameters over the period of the rainy seasons including agricultural related significantly to temperature, BOD, COD, TP and H2S. Nitrite and TDS had relationship with settlement and paddy field had relationship with pH and TSS. Moreover, only forest had relationship with DO in wet periods. The overall statistically relationships were significant in p < 0.05. This research provides perspective relationship between water quality and land cover types which is an important factor for the water resources conservation in the management plans. Keywords: water quality, land cover, surface runoff, stepwise linear regressions, water resources conservation